Special needs and early years a practitioner's guide - Wall, Kate (Los Angeles SAGE, 2011)
In the third edition of this respected and influential textbook, Kate Wall blends theory and practice with an informative and highly accessible writing style to provide a detailed analysis of provision for young children with additional needs. This book is essential reading for early years students and practitioners, and for all those working with young children with special educational needs and their families.
Previous edition: London: Paul Chapman, 2006.
Includes bibliographical references (pages 227-240) and index.
Keywords: Early childhood special education -- Great Britain